Validitas E-Modul Fisika Terintegrasi Bencana Gunung Meletus Berbasis Model Inquiry Based Learning untuk Meningkatkan Sikap Kesiapsiagaan Peserta Didik - Kurnia, Rizki (Universitas Negeri Padang, 2020)
Physics is a part of natural science that discusses natural phenomena using scientific methods. Volcanoes are one of the natural phenomena in Indonesia. The eruption of the mountain had an impact on the people around the volcano. The purpose of this study is to find out the validity of the integrated Physics e-module of the volcano eruption based on inquiry based learning to improve students' preparedness attitude. The method used in this research is research and development methods. Research and development methods are used to produce certain products, and test those products. The instrument in this study was the validity questionnaire. This validity questionnaire covers four aspects, namely the appropriateness of content, the appropriateness of presentation, the appropriateness of linguistics, and graphics. The attitude of students' preparedness needs to be improved considering that Indonesia is an area prone to volcanic eruptions. So the development of an integrated Physics e-module of the volcano eruption based on inquiry based learning to improve the attitude of students is valid.